Political communication in restoring public trust: A case study of President Prabowo’s response to the attack on TNI-UNIFIL peacekeepers by Israel - Achmad Kadafi; Irva Wike Aprisa; Edison Bonartua Hutapea (Privietlab, 2026)
The attack on TNI-UNIFIL (United Nations Interim Force in Lebanon) peacekeeping observation posts by the Israeli military in October 2024 presented a significant diplomatic and political challenge for the newly inaugurated administration of President Prabowo Subianto. This study analyses the political communication strategies employed by President Prabowo in responding to the incident and their impact on restoring both domestic and international public trust. Employing a qualitative approach through Critical Discourse Analysis (CDA) and frameworks of Agenda Setting, Framing Theory, and Political Communication Theory, this research examines official statements, press conferences, state speeches, and diplomatic communications conducted by the Indonesian government. Findings indicate that President Prabowo utilized a four-layered communication strategy: (1) nationalism and state sovereignty framing; (2) mobilization of international solidarity through multilateral diplomatic channels; (3) coordinated media narrative management; and (4) construction of assertiveness-based leadership identity. This strategy effectively increased domestic public trust by 12.3% based on post-incident surveys, while simultaneously strengthening Indonesia's position in international forums. This study contributes to the development of political communication theory in the context of diplomatic crises in emerging democratic nations. Keywords: Diplomatic Crisis, Media Framing, Political Communication, Public Trust, TNI-UNIFIL.